O memorial de formação à luz dos parâmetros cognitivos do Modelo Cultural de D’Andrade e das ideias linguísticas do Círculo de Bakhtin - Kader, Carla Callegaro Corrêa (Linguagens & Cidadania, 2017)
This paper aims to analyze three memorials of future Arts educators, using the cognitive parameters of D’Andrade Cultural Model as well as the dialogism of Bakhtin (1920- 1923). The process used to collect the memorial training was done according to the Activity Theory (LEONTIEV, 1978). We emphasize that the chosen genre is considered here a relevant tool in the context of learning of the future teachers, exploring data of the enunciation context, observing the different voices inserted in the texts, such as the academic, the literary and the familiar voices. The results show that the participants of this research based their speech in three categories: perceptions and beliefs, feelings and wishes, intentions and resolutions. In relation to the voices presented in the texts, we identified the family besides the first teacher from the elementary school as important subjects in the decisions and actions of the participants of this research.